2003
DOI: 10.1038/sj.npp.1300324
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α2 Adrenergic Receptors Suppresses Fear Conditioning: Expression of c-Fos and Phosphorylated CREB in Mouse Amygdala

Abstract: a 2 adrenergic agonists such as dexmedetomidine generally suppress noradrenergic transmission and have sedative, analgesic, and antihypertensive properties. Considering the importance of the neurotransmitter norepinephrine in forming memories for fearful events, we have investigated the acute and chronic effects of dexmedetomidine on discrete cue and contextual fear conditioning in mice. When administered before training, dexmedetomidine (10-20 mg/kg, i.p.) selectively suppressed discrete cue fear conditioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…Dexmedetomidine is preferable for immunocompromised patients, because neither lymphocyte dysfunction nor attenuated lymphocyte proliferation was found at clinically relevant plasma concentrations 20. While dexmedetomidine showed age-dependent hypnotic sensitivity, as demonstrated by potent hypnosis in neonatal rats 22, it is subhypnotic to mice at a dose of 50 µg/kg 23. The dose used in this study was lower than 50 µg/kg and exerted an antinociceptive effect on formalin-induced pain.…”
Section: Discussionmentioning
confidence: 78%
“…Dexmedetomidine is preferable for immunocompromised patients, because neither lymphocyte dysfunction nor attenuated lymphocyte proliferation was found at clinically relevant plasma concentrations 20. While dexmedetomidine showed age-dependent hypnotic sensitivity, as demonstrated by potent hypnosis in neonatal rats 22, it is subhypnotic to mice at a dose of 50 µg/kg 23. The dose used in this study was lower than 50 µg/kg and exerted an antinociceptive effect on formalin-induced pain.…”
Section: Discussionmentioning
confidence: 78%
“…The α2 adrenoceptor agonist dexmedetomidine indeed blocks fear consolidation (Davies et al, 2004), although this was tested in normal mice not in a PTSD mouse model. However, no preventive clinical PTSD studies using α2 adrenoceptor agonists have been reported.…”
Section: Preventionmentioning
confidence: 99%
“…Elevating cAMP levels leads to the activation of cAMP dependent kinases, such as MAPK, PKA and PKC, which in turn phosphorylates CREB. Phosphorylated CREB is a transcription factor that upregulates gene transcription, including immediate-early genes such as c-fos and Arc (Davies et al, 2004; Blundell and Adamec, 2007; Orman and Stewart, 2007; Canal et al, 2008). Expression of Arc protein is induced by strong synaptic activation and is quickly transported to the active dendrites to participate in synaptic remodeling during associative learning and LTP (Bramham et al, 2008; Miyashita et al, 2008).…”
Section: Introductionmentioning
confidence: 99%